Odpowiedź :
Odpowiedź:
c) 4 i 1/5 : 7/10- 1/3= 21/5 *10/7 -1/3( skracamy 21 i 7 przez 7, oraz 5 i 10 przez
5)= 3*2- 1/3= 6-1/3= 5 i 3/3-1/3= 5 i 2/3
E) ( 2 i 1/6 - 3/4) :2/3= ( 2 i 2/12 - 9/12): 2/3= ( 1 i 14/12- 9/12):2/3=
= 1 i 5/12:2/3= 17/12 *3/2( skracamy 12 i 3 przez 3)= 17/4*1/2= 17/8= 2 i 1/8
F) 2/5 * 1 i 2/3 + 4 i 2/3 : 7/9= 2/5 *5/3 + 14/3 *9/7( skracamy 5 i 5 przez 5,
oraz 14 i 7 przez 7)= 2*1/3 + 2*3=2/3+6= 6 i 2/3
G) ( 1/4 +1/3) *( 1/2-2/7)= ( 3/12 +4/12) *( 7/14- 4/14)= 7/12 * 3/14( skracamy 12 i 3
przez 3,oraz 14 i 7 przez7 )= 1/4*1/2= 1/8
H) ( 2 i 1/3 - 1 i 1/6) : ( 1 i 3/4 + 1 i 3/4 + 1 i 1/6)=( 2 i 2/6-1 i 1/6):( 2 i 6/4+1 i 1/6)=
= 1 i 1/6 : ( 3 i 1/2 +1 i 1/6)= 7/6 : (3 i 3/6 +1 i 1/6)= 7/6 : 4 i 4/6=
= 7/6 : 28/6= 7/6 * 6/28( skracamy 6 i 6 przez 6, oraz 28 i 7 przez
7= 1/4
Szczegółowe wyjaśnienie: